2020
DOI: 10.1111/cas.14327
|View full text |Cite
|
Sign up to set email alerts
|

Replisome genes regulation by antitumor miR‐101‐5p in clear cell renal cell carcinoma

Abstract: | INTRODUC TI ONRenal cell carcinoma (RCC) accounts for approximately 3% of adult malignancies and is the 12th most prevalent malignancy worldwide, with 338 000 newly diagnosed patients in 2012 and approximately 100 000 deaths annually. 1 Clear cell RCC (ccRCC) is pathologically the most common type and accounts for approximately 75% of all cases. 2 Although the prognosis is favorable with surgical resection for nonmetastatic RCC, approximately 20%-30% of RCC patients have metastatic sites at the diagnosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 39 publications
4
26
0
Order By: Relevance
“…Our functional investigations already underline this hypothesis as DONSON-depletion caused growth restriction in a time-dependent manner in our RCC cell culture model. This is in line with previous literature, where DONSON-depletion also induced apoptosis [ 16 ]. Nevertheless, it should be mentioned that DONSON's potential as a therapeutic target requires further investigation.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our functional investigations already underline this hypothesis as DONSON-depletion caused growth restriction in a time-dependent manner in our RCC cell culture model. This is in line with previous literature, where DONSON-depletion also induced apoptosis [ 16 ]. Nevertheless, it should be mentioned that DONSON's potential as a therapeutic target requires further investigation.…”
Section: Discussionsupporting
confidence: 94%
“…Recently, the tumor-suppressive miR-101-5p was shown to negatively regulate DONSON and several replisome genes in KIRC. Expression of miR-101-5p, as well as siRNA-mediated DONSON knockdown, caused cell cycle arrest, apoptosis, and impaired motility in the RCC cell lines 786O and A498 [ 16 ]. Our results are, therefore, in line with this previously published study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The A498 and 786-O human RCC cell lines were used in this study and were obtained from the Japanese Collection of Research Bioresources Cell Bank. Cell maintenance was performed as we described previously [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our RNA-sequencing-based signatures refute this concept, and our recent studies showed downregulation of both the guide and passenger strands of miRNA duplexes (e.g., miR-30c , miR-99a , miR-101 , miR-143 , miR-145 , and miR-150 ) in cancer tissues [ 10 , 11 , 12 ]. Furthermore, ectopic expression assays revealed that the passenger strand of some miRNAs, similar to the guide strand, functions as tumor-suppressive miRNAs, regulating many oncogenes intracellularly [ 13 , 14 , 15 , 16 ]. Involvement of miRNA passenger strands in the molecular pathogenesis of human cancers is a new concept, and additional research on passenger strands is needed.…”
Section: Introductionmentioning
confidence: 99%